Analysis of prescribing antibiotics knowledge among dental practitioners in Klang Valley region / Huda KH. Abdul Kader - Abdul Kader, Huda KH. (2010)
There is a major concern with ongoing exaggerated use of antibiotics in dental practice and the emergence of resistant bacterial strains. In recent it years, dentists have reported a shift from narrow-spectrum to broad-spectrum antibiotic prescriptions due to increasing antibiotic resistance. In addition, the empiric use of ntibiotic prophylaxis for dental procedures. especially those that cause bleeding in the mouth has become a reasonably well established practice among dental professionals. This misuse of antibiotics is no longer acceptable and the dentists must prescribe antibiotics in a judicious and prudent manner to avoid the adverse effects of antibiotics. The main aims of this study are to assess the knowledge among dental practitioners in the use of antibiotics for patients with acute dental infection and to compare their prescription with the Malaysia National Clinical Guidelines (MNCG) 2003 investigates the prescribing habits of dental practitioners for some clinical dental situations, determine their antibiotic prescribing knowledge for prophylactic purpose and compare their prescription with American Heart Association (AHA) guidelines 2008, assess their knowledge regarding the need of cardiac diseases to antibiotic cover and also to determine their knowledge regarding antibiotic cover for dental procedures in patients at risk of infective endocarditis.